Academic Entrepreneurship and Community Engagement: Scholarship in Action and the Syracuse Miracle - Kingma, Bruce (Cheltenham, U.K. and Northampton, Mass.: Elgar, 2011)
Eleven papers explore research in entrepreneurship and community engagement in the context of Syracuse University's Scholarship in Action Model, which emphasizes sustainable campus-community entrepreneurial partnerships and applied research on the outcomes of these. Papers discuss the five keys to success in academic entrepreneurship; transforming a professional curriculum through engagement with practice–the Global Enterprise Technology Program at Syracuse University; tapping our fountain of youth–the guiding philosophy and first report on the Syracuse Student Startup Accelerator; Syracuse University Technology Commercialization Clinics; community development law and legal education; the Syracuse Miracle–inspiring entrepreneurs through conversations; the South Side Newspaper Project; bridging a traumatic past to an envisioned future–a case study of social entrepreneurship; inclusive entrepreneurship; the role of information and motivation in the process of innovation; and students serving as catalysts within a teacher education innovation.
Accès 1 usager à la fois sur ebook Central
Keywords: Communauté d'innovation; Engagement communautaire; Entrepreneuriat; Idéation; dialogue et maillage; Partenariat; Réservé UdeM; Rôle des universités; Transfert; Université; États-Unis